OPEC, Shale Oil, and Global Warming - On the importance of the order of extraction - Hassan Benchekroun; Gerard van der Meijden; Cees Withagen (Tinbergen Institute, 2017)
We show that OPEC's market power contributes to global warming by enabling producers of relatively expensive and dirty oil to start producing before OPEC reserves are depleted. We fully characterize the equilibrium of a cartel-fringe model and use a calibration to examine the importance of this extraction sequence effect. While welfare under the cartel-fringe equilibrium can be significantly lower than under a first-best outcome, almost all of this welfare loss is due to the sequence effect. Moreover, the recent boom in shale oil reserves may reduce social welfare and renewables subsidies can increase the carbon content of current extraction.
Keywords: Q31; Q42; Q54; Q58; 330; cartel-fringe; climate policy; non-renewable resource; Herfindahl rule; limit pricing